Workers, Strikes, and Pogroms : The Donbass-Dnepr Bend in Late Imperial Russia, 1870-1905 - Wynn, Charters, 1953- (Book collections on Project MUSE., 1992)
In this major reassessment of Russian labor history, Charters Wynn shows that in Imperial Russia's primary steel and mining region the same class that posed a powerful challenge to the tsarist government also undermined the revolutionary movement with its pogromist violence. From the last decades of the nineteenth century through Russia's First Revolution in 1905, the revolutionary parties succeeded in inciting the predominantly young, male ""peasant-workers"" of the Donbass-Dnepr Bend region to take part in general strikes, rallies, and armed confrontation with troops. However, the parties